Relationships between succes orientation, self efficacy on scientific research and metacognitive thinking skills - Tuncer, Murat; Bahadır, Ferdi (My University, 2018)
In this study, relations between metacognition, achievement orientation and scientific research self-efficacy were investigated. Research findings attested that metacognitive thinking skills play a mediator effect between success orientations and self-efficacy on scientific research. Further to that, success orientation rendered a positive impact on the perception of scientific research self-efficacy and success orientations positively affected meta-cognitive thinking. On the other hand, self-efficacy on scientific research had a negatively insignificant effect on meta-cognitive thinking skills. At the end of this research, it can be suggested to instructors that in tracking and learning processes in their class if they employ activities that stimulate metacognitive thinking skills after completing success-orientated activities, positive feedbacks could be obtained on students' perception of scientific research self-efficacy level. Aside from that since the paths between divergent and success orientations; problem solving, decision making, alternative evaluation and metacognitive thinking and conclusion and discussion, method and literature review and perception of scientific research self-efficacy show; it can be argued that these correlational results would be safely employed in academic processes.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Success orientation; Self-efficacy on scientific research; Metacognitive thinking skills; Structural equation model